2013
DOI: 10.1111/age.12104
|View full text |Cite
|
Sign up to set email alerts
|

A frameshift mutation in the melanophilin gene causes the dilute coat colour in rabbit (Oryctolagus cuniculus) breeds

Abstract: In rabbit, the dilute locus is determined by a recessive mutated allele (d) that causes the dilution of both eumelanic and pheomelanic pigmentations. In mice, similar phenotypes are determined by mutations in the myosin VA, Rab27a and melanophilin (MLPH) genes. In this study, we investigated the rabbit MLPH gene and showed that a mutation in this gene appears responsible for the dilute coat colour in this species. Checkered Giant F1 families segregating for black and grey (diluted or blue) coat colour were fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 37 publications
(45 reference statements)
0
35
0
Order By: Relevance
“…Studies have shown that the protein complexes encoded by MLPH, RAB27A, and MYO5A are required for melanosome transport (Ménasché et al, 2003). In several species, such as humans, cats, dogs, horse, mink, rabbit, and quail, defects in MYO5A, RAB27A, and MLPH were found to cause a phenotypically identical pigmentary dilution (Wilson et al, 2000;Matesic et al, 2001;Ménasché et al, 2000Ménasché et al, , 2003Philipp et al, 2005;Ishida et al, 2006;Bed'hom et al, 2012;Cirera et al, 2013;Fontanesi et al, 2014). Results of the association analysis showed that only one SNP in MLPH was significantly associated with the gray plumage color phenotype, suggesting that the MLPH gene might be closely associated with the gray plumage color phenotype.…”
Section: Association Of the Snp With Anyi Tile-like Gray Phenotypesmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that the protein complexes encoded by MLPH, RAB27A, and MYO5A are required for melanosome transport (Ménasché et al, 2003). In several species, such as humans, cats, dogs, horse, mink, rabbit, and quail, defects in MYO5A, RAB27A, and MLPH were found to cause a phenotypically identical pigmentary dilution (Wilson et al, 2000;Matesic et al, 2001;Ménasché et al, 2000Ménasché et al, , 2003Philipp et al, 2005;Ishida et al, 2006;Bed'hom et al, 2012;Cirera et al, 2013;Fontanesi et al, 2014). Results of the association analysis showed that only one SNP in MLPH was significantly associated with the gray plumage color phenotype, suggesting that the MLPH gene might be closely associated with the gray plumage color phenotype.…”
Section: Association Of the Snp With Anyi Tile-like Gray Phenotypesmentioning
confidence: 99%
“…Studies in chicken and quail showed that the lavender plumage color dilution phenotype was caused by a mutation in the MLPH gene (Vaez et al, 2008;Bed'hom et al, 2012), and that the protein complexes encoded by MLPH, RAB27A, and MYO5A were required for melanosome transport. In fact, mutations in MLPH, RAB27A, and MYO5A can all lead to the dilution phenotype in animals (Matesic et al, 2001;Ménasché et al, 2003;Philipp et al, 2005;Ishida et al, 2006;Bed'hom et al, 2012;Cirera et al, 2013;Fontanesi et al, 2014). Presumably, the "gray" phenotype is derived from the black phenotype (i.e., black feathers, shanks, skin, beak, and comb).…”
Section: Introductionmentioning
confidence: 99%
“…, , ; Fontanesi et al . , , ) and (iii) a first copy number variation genomic map has been obtained using array comparative genome hybridization in a few rabbits (Fontanesi et al . ).…”
Section: Data and Results Obtained By Sequencing The Two Reduced Reprmentioning
confidence: 99%
“…Obtained PCR products were sequenced using the Big Dye v3.1 cycle sequencing kit (Applied Biosystems) as previously described (Fontanesi et al . ). Sequencing reactions were loaded on an ABI3100 Avant sequencer (Applied Biosystems).…”
Section: Rabbits Genotyped For the Tyrp1 G41360196g>a Mutationmentioning
confidence: 97%
“…), a deletion in the melanophilin ( MLPH ) gene causes the dilute coat colour phenotype (Fontanesi et al . ), and mutations in the tyrosinase ( TYR ) genes determine alleles of the albino ( C ) locus (Aigner et al . ).…”
Section: Rabbits Genotyped For the Tyrp1 G41360196g>a Mutationmentioning
confidence: 99%